Grazing induced biodiversity in the highland ecozone of East Africa - Woldu, Z.; Mohamed-Saleem, M.A. (Elsevier, 2000)
The species composition of grazing lands can be influenced by livestock and grazing pressure. A study on manure seed bank was conducted in Ghinchi highland Research Site in Ethiopia between 1995 and 1997. the data on species composition and life-form of the plants germinating in pots receiving air dried manure were compared with species composition of experimental plots in natural grassland subjected to varying grazing intensity. There was significant difference among the species composition of grazed and non grazed grasslands and the manure seed bank (p=0.01). The life-forms of the species also showed variation. There were more families and species in the natural grassland vegetation than indicated in the manure seed bank. The manure seed bank had more annuals than the natural grassland vegetation. The species composition and life-forms in the manure seed bank showed variation with time and this corresponded with the seasonal variation in the grassland, which had a direct relationship with the rainfall pattern. The study showed that livestock play a major role in maintaining the biodiversity of grassland vegetation by spatial and temporal dispersion of readily germinating seeds in their manure. The use of manure to improve soil fertility should be weighed cautiously against the introduction of weeds into crop fields, although weeds are important feed resource for livestock in land-constrained areas. There is therefore the need for developing manure management practices so that the benefits can be optimised and the undesirable effects can be minimised.